Isolation, Identification and In-Vitro Fermentation Activity of Cellulolytic Bacteria from the Gut of Termites - Ramin, Mohammad (2008)
Termites are known for their ability to digest high lignocellulolytic compounds, such as wood and fiber materials. Ruminants with the aid of their microorganisms are able to digest fiber materials, however the percentage of digestion is not so high. Therefore, the main objectives of this study were to isolate and identify cellulolytic bacteria from the termites gut and to determine the ability of these bacteria to improve the digestibility of fibrous feed materials by the rumen microflora using the in-vitro gas production technique. In this study, cellulolytic bacteria isolated from the gut of termites were used to mix with the rumen microflora on fiber material digestion. Termites were obtained from decayed plant materials and nests from different locations in the vicinity of Universiti Putra Malaysia (UPM). They were identified as the lower termite Coptotermes curvignathus (Holmgren) and the higher termite Macrotermes gilvus (Hagen). Cellulolytic bacteria from the gut of the lower termite; Coptotermes curvignathus (Holmgren) was isolated. The isolates were cultured aerobically in a medium containing carboxymethylcellulose (CMC) at temperature of 30°C. The five isolates obtained were identified based on the Biolog reader chemical test, Bergy' s Manual and 1 6S rRNA sequence homology. The species were identified as: Bacillus cereus (isolate 1), Acinetobacter baumanni (isolate 5), Enterobacter aerogenes (isolate 2), Enterobacter cloacae (isolate 3) and Chryseobacterium kwangyangense (isolate 4). The Gene Bank NCBI/EMBL accession numbers for the bacterial isolates are EU294508, EU332791, EU305608, EU305609, and EU 169201 respectively. Acinetobacter baumanni isolate 5 is an aerobic bacterium, while the other four species are facultative anaerobes. The first invitro experiment by the gas production technique was conducted to examine the digestion and volatile fatty acid production by the five bacterial species grown in the rice straw medium. There were significant differences (P<0.05) in dry matter loss (DM) of rice straw and acetic acid concentration among the five bacterial species. A cinetobacter baumanni isolate 5 showed the highest fermentation activity (7.76 mM). The second in-vitro experiment also by gas production technique, which was conducted to determine the effect of adding rumen fluid microflora on rice straw digestion. The bacterial cultures were standardized to an OD of 0.5 (108 CFU/ml) before adding to the rumen fluid micro flora. Rumen fluid was obtained from a fistulated cattle maintained on a grass diet. The facultative bacteria tested were C. kwangyangense isolate 4, E. cloacae isolate 3 and E. aerogenes isolate 2. Digestion of rice straw by rumen fluid microflora was determined with or without adding individual cultures of termites gut bacterial species.